The levels of osteopontin in human milk of Chinese mothers and its associations with maternal body composition - Huijuan Ruan; Qingya Tang; Xuan Zhao; Yajie Zhang; Xuelin Zhao; Yi Xiang; Wei Geng; Yi Feng; Wei Cai (Food Science and Human Wellness, 2022)
Objective: This study explored the content and change trend of osteopontin (OPN) in breast milk and analyzed the relationship between OPN in breast milk and maternal body composition. Methods: Breast-feeding mothers were recruited in Xinhua Hospital to collect breast milk and provide pertinent information. The content of OPN in breast milk was determined by enzyme-linked immunosorbent assay (ELISA). Determination of protein content in human milk was performed via the BCA method. The maternal body composition was determined by the bioelectrical impedance method. Serum glucocorticoid receptor α, adiponectin, insulin, and leptin were determined by ELISA. SPSS 25 was used for statistical analysis. Results: In the longitudinal cohort, 106 mothers provided 318 milk samples at different lactation periods. The results indicate that the OPN showed dynamic changes. OPN levels were (343.2 ± 163.5) mg/L during 114 days postpartum, (228.4 ± 121.5) mg/L during 24 months postpartum, and (204.8 ± 100.6) mg/L during 57 months postpartum. The content of OPN was very high in the first 114 days postpartum and then decreased. Compared with early postpartum milk, the OPN content of mature milk showed a significant relationship with maternal weight-related parameters. Additional body composition analysis was performed in 88 women at the mature milk phase. The results show that the OPN in milk is related to the mother’s body composition, especially the content of skeletal muscle mass, but not to relevant humoral factors. Conclusions: The levels of OPN in human milk of Chinese mothers showed dynamic changes with the extension of lactation time. The OPN in human milk was related to the mother’s body composition but not related to related humoral factors.